Correlation of ages, lithologies and structures in Tornio - Haparanda area - Kaartinen, Maiju (fi=Turun yliopisto|en=University of Turku|, 2017)
The aim of this study is to correlate the ages, lithological units, and structures within the Tornio – Haparanda area, across the national border between Finland and Sweden. The area, generally known as the Peräpohja Belt, consists mainly of well-preserved Proterozoic supracrustals, which have been deposited on an Archean basement. They are cut by several sills, dykes, and larger intrusions, for example the Haparanda and Lina Suites. The metamorphic grade in the area is mainly low. The field work took place during the summer 2014, the main research methods being structural bedrock mapping and sampling. Geochemical analyses were conducted on and petrographical observations were made from eight of the samples taken from the Swedish side of the study area. For five of these samples also LA-ICP-MS method was used to yield U-Pb ages. The collected information was combined with the existing datasets. Based on the structural measurements, age results, geochemical analyses, literature, and lithological and geophysical maps from each of the countries, some correlation models were made. Three of the age determination samples locate on the Proterozoic Lina and Haparanda Suites’ intrusive. The remaining two are situated within the Archean Kukkola Gneiss Complex. The results highly support the large-scale magmatism at 1.88 Ga though they somewhat question the earlier division between the Lina and Haparanda Suites. The age difference between the two samples within the Kukkola Gneiss Complex proves that there has been more than one intrusive event during the Archean.